2008
DOI: 10.1038/ajh.2008.300
|View full text |Cite
|
Sign up to set email alerts
|

Low Anxiety Males Display Higher Degree of Salt Sensitivity, Increased Autonomic Reactivity, and Higher Defensiveness

Abstract: Low-anxiety subjects were characterized by a higher degree of salt sensitivity and increased autonomic responsiveness. Defensiveness was also shown to be elevated in this group and might be the underlying psychological trait explaining these findings. Future research on the associations of anxiety and cardiovascular risk should implement measurement of defensiveness in order to identify these subjects at potential risk for cardiovascular disease despite self-reports of low anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…It should be noted that the mean TA scores of the three groups were similar to scores obtained with similar categorization methods [ 3 ] and with different categorization methods (quartiles) [ 64 ]. Moreover, the mean TA scores of our samples are comparable to the TA scores of average Chinese college students.…”
Section: Discussionsupporting
confidence: 61%
“…It should be noted that the mean TA scores of the three groups were similar to scores obtained with similar categorization methods [ 3 ] and with different categorization methods (quartiles) [ 64 ]. Moreover, the mean TA scores of our samples are comparable to the TA scores of average Chinese college students.…”
Section: Discussionsupporting
confidence: 61%
“…The manometer test is a well-established standardised computer-based information processing task performed under time pressure (Buchholz et al 2003;Deter et al 2001;Weber et al 2007Weber et al , 2008Zimmermann-Viehoff et al 2008). All tests and instructions were given on a computer monitor.…”
Section: Manometer Testmentioning
confidence: 99%
“…This cutoff was found to be the median for trait anxiety in a previous study involving young healthy males recruited in Berlin. 28 We decided to recruit subjects with elevated trait anxiety because we assumed that such subjects would be characterized by a higher desire for anxiety relief, possibly increasing their proneness to respond to a placebo intervention aimed to reduce stress and anxiety. This assumption was based on findings from placebo analgesia studies, where desire for pain relief was shown to contribute significantly to the variance in placebo responses.…”
Section: Methodsmentioning
confidence: 99%